Efek Pemberian Minyak Atsiri Daun Sirsak (Annona muricata Linn) terhadap Penurunan Kadar Tumor Necrosis Factor Alpha (TNF-α) Hepar Tikus Wistar Jantan yang Diinduksi Rifampisin - Shofiyyatunnisa Wuslatush Sholihah; Marindra Firmansyah; Dini Sri Damayanti (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2018)
AbstractIntroduction: Rifampicin is one of anti-tuberculosis drugs are reported to have hepatotoxic effects through increasing ROS (Reactive Oxygen Species) so thattriggering necrosis of liver cells and stimulates the formation of TNF-α. Essential oil of Annona muricata Linn. contains linalool, β-caryophyllen, trans-caryophyllen, germacrene A, germacrene B, germacrene D, sesquisterpene, β-canidine, γ-canidine. The objective of this study is to investigate the effect of essential oil of Annona muricata Linn. on levels of Tumor Necrosis Alpha(TNF-α) liver in male wistar rats which induced by rifampicin.Methods: This was an invivo experimental study with control group post test only design and use 25 male wistar rats and divided into 5 groups, they are KN (corn oil), KP (Rifampicin), P1 (Rifampicin + Essential oil 1,5%), P2 (Rifampisin + Essential oil 3%), P3 (Rifampisin + Essential oil 6%) for 6 weeks and then levels of TNF-α liver will be checked. Analysis of the data using One Way (ANOVA) test and then tested by post hoc test using Least Significant Difference (LSD). The result significant if p<0,05.Result: Induced rifampicin can increased levels of TNF-α liver than group KN (p<0,05). Treatment of essential oil of Annona muricata Linn. on P1, P2, and P3 can reduced levels of TNF-α liver than group KP (p<0,05). Allegedly this is due to the active ingredient in the essential oils act as antioxidants and antiinflammatory.Conclusion: Essential oil of Annona muricata Linn. at all doses can reduced levels of TNF-α liver in male wistar rats which induced by rifampicin.Keywords:rifampicin,essential oil of Annona muricata Linn., TNF-α liver